ANÁLISIS DE LA CARTERA DE CRÉDITO DE LA COOPERATIVA DE AHORRO Y CRÉDITO “CRISTO REY” DE LA CIUDAD DE LOJA, PERIODOS: 2016-2018 Y PROPUESTA DE MEJORA - Merchan Lima, Yomira Viviana (2019)
This thesis work called. “Analysis of the Credit Portfolio of the Savings and Credit Cooperative “Cristo Rey” of the city of Loja, periods: 2016-2018 and proposed improvement.”, Was developed with the purpose of establishing a diagnosis of the economic situation- financial, through the vertical, horizontal analysis and the application of financial indicators to determine existing weaknesses and finally the formulation of strategies that contribute to reduce its risk and improve administrative and financial management. In this context, the investigation began with the collection of the information of the cooperative, in a second stage a diagnosis was made, using the balances to know the economic-financial situation. With the vertical analysis it was possible to determine its structure to the year 2018, where it is evidenced that its assets amount to 9,263,835.02 dollars, which are financed in 71% by public funds and 29% contribution of partners. With the horizontal analysis, the existing variations of its Assets, Liabilities, Equity were demonstrated demonstrating sustainable growth. Likewise, several indicators established by the Superintendence of Popular and Solidarity Economy (SEPS) were applied, where it was known that its liquidity is low of 8.22 compared to 19.79%; with regard to their productive assets they are in the acceptable parameter of 88.70%; its delinquency level is high of 8.93 compared to the established parameter that is 5%. Subsequently, the administrative aspects were evaluated, where a survey was applied to determine the strengths and weaknesses that the cooperative has when granting and recovering a loan. Finally, an Improvement Plan is proposed, where strategies are presented for the benefit of the cooperative which will help to fulfill the established goals and objectives, as well as to have an adequate management of its Cooperative.